Innovative regenerative therapy for refractory postoperative esophageal anastomotic stenosis in children - Yasushi Fuchimoto (Journal of Pediatric Surgery Open, 2024)
Autologous oral mucosa-derived epithelial cell sheet transplantation was devised as a new treatment for refractory postoperative anastomotic stenosis in patients with congenital esophageal atresia (CEA) and congenital esophageal stenosis (CES). Transplantation therapy was performed on three patients with refractory postoperative anastomotic stenosis who had undergone endoscopic balloon dilatation (EBD) at least twice in one year and at least five times in total. Epithelial cell sheets were prepared from the patients' oral mucosa and transplanted over the esophageal wounds caused by EBD using a specially developed transplantation device. After transplantation, the patients were followed for 48 weeks. Subject 1 underwent two transplantations and showed temporary improvement in stenosis, but required periodic EBD and eventually had the stenotic area removed. Subject 2 did not require EBD for more than two years post-transplantation; Subject 3, until one year after transplantation. Both Subject 2 and Subject 3 experienced improvement in the passage of food and drink and were able to consume a regular diet as opposed to a full liquid diet. These results suggest that cell sheet transplantation therapy is effective in some cases.Trial registration: UMIN, UMIN000034566, registered 19 October 2018, https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000039393.